Let Me Off At The Top! : My Classy Life and Other Musings - Burgundy, Ron (London Century, 2013)
The popular character from the "Anchorman" movies shares stories of his childhood and the events that led him to choose a career in the news business; personal anecdotes about the women in his life and his legendary news team; and advice on a variety of topics.
Include Illustration
Keywords: Television broadcasting of news -- Burgundy, Ron -- Television news anchors